Hepatoprotective Activity of Herbal Preparation (Hp-4) against Alcohol Induced Hepatotoxicity in Mice - Padmanabhan, P.; Jangle, S. N. (International Journal of Applied Sciences and Biotechnology, 2014)
Free radicals include both Reactive Oxygen Species (ROS) and Reactive Nitrogen Species (RNS).When free radicals are produced in a regulated manner in a healthy human body it is scavenged efficiently by antioxidant defense system. But excess generation of pro-oxidants by continuous chain reaction in the form of ROS and RNS cause several human diseases. The shift of the balance in the favour of pro-oxidants results in a condition called “oxidative stress”. Alcohol is primarily metabolized in the liver to generate ROS and RNS, leading to diseases such as cirrhosis, fatty liver and chronic hepatitis. Alcohol induced damage is associated with oxidative stress. The excess generation of prooxidants and reduced antioxidant levels provide an effective model of Hepatotoxicity which is noteworthy. Recent trend is to discover polyherbal formulation of medicinal plants which have hepatoprotective function. In the present study 80% alcoholic extract of leaves of Aloe vera, Bacopa monniera, Moringa oleifera and rhizome of Zingiber officinale were utilized to prepare Herbal Preparation or HP-4.Further the hepatoprotective effects of HP-4 was tested in alcohol induced Hepatotoxicity in mice. Silymarin is a well known hepatoprotective drug was used as a standard for comparison. Biochemical and histopathological studies provided ample evidence that HP-4 provided a hepatoprotective role in alcohol induced hepatotoxicity which was comparable to drug Silymarin. The presence of phytochemicals in HP-4 provided a synergistic, supra-additive and co-operative effects in the hepatoprotective function in alcohol induced hepatotoxicity mice model. DOI: http://dx.doi.org/10.3126/ijasbt.v2i1.9346 Int J Appl Sci Biotechnol, Vol 2(1): 50-58